Synchronous Leisure, Jointness and Household Labor Supply - Daniel Hallberg (Uppsala University, Department of Economics, 2002)
This paper examines the synchronous leisure of spouses and the extent to which spouses spend time together. The time budget data set used in this paper allows for a distinction between simultaneous time-use of spouses and the actual time that spouses meet. A comparison between couples and matched singles suggests that only about 12 percent (45 minutes per day) of the synchronous leisure is caused by active synchronization. Spouses' decisions about market work and leisure timing are very interdependent during most hours of the day. The results also suggest that, conditional on synchronous leisure, parents with high incomes spend more time together than others, while more educated people allocating less time to their spouses.
urn:nbn:se:uu:diva-2231
Keywords: D10; J22; 330; Time-use; synchronous leisure; working hours; togetherness; family economics; statistical matching; Zeitverwendung; Familie; Arbeitsangebot; Familienökonomik; Theorie; Zeitverwendung; Schweden